Fragment Screening Yields a Small‐Molecule Stabilizer of 14‐3‐3 Dimers That Modulates Client Protein Interactions. (19th July 2022) - Brink, Hendrik J.; Riemens, Rick; Thee, Stephanie; Beishuizen, Berend; da Costa Pereira, Daniel; Wijtmans, Maikel; de Esch, Iwan; Smit, Martine J.; de Boer, Albertus H.
Abstract: The development of protein‐protein interaction (PPI) inhibitors has been a successful strategy in drug development. However, the identification of PPI stabilizers has proven much more challenging. Here we report a fragment‐based drug screening approach using the regulatory hub‐protein 14‐3‐3 as a platform for identifying PPI stabilizers. A homogenous time‐resolved FRET assay was used to monitor stabilization of 14‐3‐3/peptide binding using the known interaction partner estrogen receptor alpha. Screening of an in‐house fragment library identified fragment 2 (VUF15640) as a putative PPI stabilizer capable of cooperatively stabilizing 14‐3‐3 PPIs in a cooperative fashion with Fusicoccin‐A. Mechanistically, fragment 2 appears to enhance 14‐3‐3 dimerization leading to increased client‐protein binding. Functionally, fragment 2 enhanced potency of 14‐3‐3 in a cell‐free system inhibiting the enzyme activity of the nitrate reductase. In conclusion, we identified a general PPI stabilizer targeting 14‐3‐3, which could be used as a tool compound for investigating 14‐3‐3 client protein interactions. Abstract : A fragment library screen identified fragment 2 as a novel non‐covalent protein‐protein interaction stabilizer targeting 14‐3‐3 dimers. Fragment 2 can act cooperatively with Fusicoccin‐A, resulting in enhanced binding to 14‐3‐3 client proteins such as the estrogen receptor alpha.